EFFECT OF WORK LIFE POLICY, WORK INVOLVEMENT AND CONFLICT OF WORKING FAMILY TO TURNOVER INTENTIONS ON EMPLOYEES - Moh. Abd. Rahman; Siti Maysaroh (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2020)
Introduction: This study aims to determine the effect of Worklife-Policies, Job Involvement, and Work-Family Conflict on Turnover Intention of employees at PT Sinar Bodhi Cipta, Tanjungpinang. This type of research uses quantitative descriptive method. The sample technique used in this study was the distribution of proportion sampling. Methods: The data analysis method used consisted of testing the quality of the data (validity and reliability). Classic assumption test (normality, heteroscedasticity, multicolonierity, and autocorrelation) Results: The results obtained can be concluded that the work-life policies, Job Involvement, and Workfamily Conflict variables partially or simultaneously have a positive and significant effect on employee turnover intention at PT Sinar Bodhi Cipta, Tanjungpinang with a R square contribution of 73.1%.